2009
DOI: 10.1136/bjo.2008.148932
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic retinoblastoma: single institution experience over two decades

Abstract: This retrospective review confirms a curable strategy based on local treatment and conventional plus high-dose chemotherapy. Patients with CNS involvement remain incurable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 25 publications
0
26
0
Order By: Relevance
“…Even with ultrasound, necrotic tumour causing uveitis or phthisis was difficult to detect. CT scanning and cerebrospinal fluid cytology would be ideal to detect intracranial extension but were impractical or impossible in this setting and would not affect outcome 8. Fine needle aspiration was not attempted in case it spread tumour cells, though it has some advocates.…”
Section: Discussionmentioning
confidence: 99%
“…Even with ultrasound, necrotic tumour causing uveitis or phthisis was difficult to detect. CT scanning and cerebrospinal fluid cytology would be ideal to detect intracranial extension but were impractical or impossible in this setting and would not affect outcome 8. Fine needle aspiration was not attempted in case it spread tumour cells, though it has some advocates.…”
Section: Discussionmentioning
confidence: 99%
“…However, retinoblastoma occurring at a different site after few months/years of primary treatment is very rare, and only few such cases are reported in the literature. (2)(3)(4)(5)(6) Only two cases of metastatic retinoblastoma in the liver has been reported earlier by Cullen et al (2) To the best of our knowledge, we report the first case of metastasis in the abdomen (retro uterine space) in a child with retinoblastoma who presented with abdominal mass after fifteen months of post enucleation radiotherapy to the left orbit.…”
Section: Introductionmentioning
confidence: 59%
“…In a retrospective study of retinoblastoma cases diagnosed over 20 year period, Cozza et al (5) from Italy reported four cases of metastatic retinoblastoma in orbit, cerebrospinal fluid (CSF), meningeal (6 months from diagnosis); CSF, meningeal (12 months from diagnosis); pineal gland (15 months from diagnosis); and orbit, bone, bone marrow (6 months from diagnosis).…”
Section: Discussionmentioning
confidence: 99%
“…[1] Orbital retinoblastoma is one of the major contributors to mortality and carries a poor prognosis for life. [2345] The presence of orbital invasion is associated with 10–27 times higher risk of metastasis when compared to cases without orbital extension. [567] The frequency of metastatic retinoblastoma ranges from 4.8 to 11%.…”
mentioning
confidence: 99%
“…[567] The frequency of metastatic retinoblastoma ranges from 4.8 to 11%. [23] The presenting signs and symptoms are quite variable and depend on the site or sites of involvement. The common sites of extraocular retinoblastoma include the orbit, preauricular nodes, bones, central nervous system (CNS) and liver.…”
mentioning
confidence: 99%